Public health education post-COVID-19: A proposal for critical revisions - Ghaffar, Abdul; Rashid, Sabina Faiz; Wanyenze, Rhoda Kitti; Hyder, Adnan A (BMJ Journals, 2022)
This article was published in the BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. http://creativecommons.org/licenses/by-nc/4.0/] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2021-005669 The Journal's website is at: https://gh.bmj.com/content/6/4/e005669